Youth‐oriented outcomes of education, employment and training interventions for upcoming youth: Protocol for a discrete choice experiment. Issue 4 (18th September 2020) - Hawke, Lisa D.; Hayes, Em; Iyer, Srividya; Killackey, Eóin; Chinnery, Gina; Gariépy, Geneviève; Thabane, Lehana; Darnay, Karleigh; Alagaratnam, Akosua; Tucker‐Kilfoil, Stephanie; Moxness, Katherine; Hachimi‐Idrissi, Najia; et al.
Abstract: Aim: The issue of youth who are not engaged in education, employment or training has been a focus of policymakers for decades. Although interventions exist for these youth, they often measure success in ways that fail to capture what youth seek to gain. The project aims to address this gap by assessing youth‐oriented outcomes for interventions targeting upcoming youth. Acknowledging the stigma attached to the deficit‐based notion of not engaged in education, employment or training, hereafter we refer to 'upcoming youth', a term coined by youth partners on the project. This study asks what youth want to achieve by participating in an intervention for upcoming youth, with a view to guiding service and research design. Methods: A mixed‐methods discrete choice experiment will be conducted with youth engaged as partners. A qualitative (focus group) stage will be conducted to design discrete‐choice experiment attributes and levels. The experiment will be piloted and administered online to approx. 500 youth (aged 14‐29) across Canada to identify the outcomes that youth prioritize for interventions. Latent class analyses will then be conducted to explore clusters of outcomes that different groups of youth prioritize. Conclusions: From a strengths‐based recovery‐oriented framework, hearing the voices of the target population is important in designing and evaluating services. This youth‐oriented research project will identify the intervention outcomes that are the highest priority for upcoming youth. Findings will inform the development, implementation and testing of interventions targeting relevant outcomes for youth who are not engaged in education, employment or training.